IMPACT OF ARTIFICIAL INTELLIGENCE TECHNOLOGY ON ACCOUNTING PROFESSION - Burhanuddin Alghafiqi; Enjat Munajat (Universitas Airlangga, 2022)
The development of Artificial Intelligence technology has changed theaccounting profession. This paper provides a comprehensive overviewof the latest developments in Artificial Intelligence, Big Data, MachineLearning used in business practices in the accounting professionworldwide. This paper explores the evolution of the accountingprofession following the latest technological developments and assessesthe impact of its development in the future. Challenges and opportunitiesposed by Artificial Intelligence relating to accounting professionals andthe process of accounting education. This study uses a normativejuridical approach with library studies with secondary data. This paperprovides an overview of how accounting educators and professionalsrespond to these technological developments and provides furtherdiscussion on what accounting professions, institutions and graduatesshould do to face the challenges of change caused by technologicaldevelopments.